INTERVENTION IN THE ADULT UNITS SECTOR OF THE SINGLE HEALTH SYSTEM OF A PHILANTHROPIC HOSPITAL IN THE CITY OF PORTO ALEGRE IN THE STATE OF RIO GRANDE DO SUL AFTER SARS-COV2 PANDEMIC: AN EXPERIENCE REPORT - Coelho Neto, Camila Alencar (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
It is well known that routines in sectors of hospitalization units with medium and low complexity patients that have a high number of employees are easily lost over time. Turnover, insufficient training, lack of direct supervision and sometimes even the lack of commitment of these same employees put common activities in the nursing area at risk, making the provision of patient care less safe. Poor management and the increase in unforeseen serious complications observed in a short space of time made it important to have a quick and objective intervention with the aim of rescuing and even correcting routines already carried out. With much more than 100 beds, divided into rooms, with 2 (two) to 4 (four) beds, it becomes almost a separate hospital. This report aims to elucidate the 43 days of active damage minimization methodology in the hospitalization unit sector.